Overview of social assessment methods for the economic analysis of cultural heritage investments - Sanja Tišma; Aleksandra Uzelac; Daniela Angelina Jelinčić; Sunčana Franić; Mira Mileusnić Škrtić (Journal of Risk and Financial Management, 2022)
This paper provides an overview of methods for assessing social impacts, their achievements, and possibilities of application in everyday practice for assessing the worth of investments in cultural heritage conservation, as well as its sustainable use. It gives an overview of available methods for social assessment and points to a set of interdisciplinary indicators by which those impacts can be evaluated. Possibilities to use social impact analysis in the assessment of cultural heritage are presented in this paper through two case studies in the Republic of Croatia: the implementation of social evaluation management plan for the old town of Buzet and the evaluation of social effects of investing in the museum Ivana's House of Fairy Tales. Some qualitative indicators of the collected surveys related to social effects are described, while the analysis of the availability of such indicators and the scientific basis of the collected answers are provided. In conclusion, the contribution of the methodological tools used and social impact assessments in the evaluation of cultural heritage interventions are presented, while suggestions are made for various decision- makers on those broader methods and benefits compared with the use of only financial and economic impact evaluations.
Keywords: 650; heritage evaluation; social performance evaluation; sociologic impact assessment; sociological analytical methods